Pengendalian Banjir Pada Kawasan Mutiara Witayu Kecamatan Rumbai Pekanbaru - Sovia Revina; Bambang Sujatmoko; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Regions Mutiara Witayu is an area with low ground, where not all runoff from rainwater can flow by gravity into the Siak River, when the high tide happen on Siak River during the rainy season there will be some back waters, so the water that should be drainaged to Siak River become overflow. This study aims to determine the capacity of the pump to serve the existing flood volume. From the calculation of flood volume that can be accommodated by the reservoir is at 5050, 876 m3. To overcome the flood in the area Mutiara Witayu completely due to R5, R10 and R25 without causing inundation by using a pump with a capacity of 6 m3 / sec. The using of 5 m3 /sec pump’s power can be used to solve the flood due to R5, R10 and R25 in the Regions Mutiara Witayu with 2908.981 m3 storage capacity will be required.Keywords: flood, ponds reservoirs, pumps